'Intimacy, informalization and intersecting inequalities: tracing the linkages'. (3rd April 2018) - Peterson, V. Spike
ABSTRACT: This essay traces linkages among the intimacy of familial household relations, the informalization and market dynamics of capitalist economies, and the intersection of multiple inequalities within and between state/nations. I also explore how informality is not only gendered but inextricably racialized. The latter is rarely addressed, much less integrated, in conventional accounts of informality. Yet it is a particularly urgent consideration in the context of today's between- and within-nation inequalities and their corollary harms, resentments, violence and conflicts. I begin by clarifying the thematic foci of intimacy, informality and intersectionality, and why I foreground them in this essay. I turn next to why state/nations are central features in my account, beginning not in the modern era but millennia ago with the earliest known 'archaic' states and their unprecedented regulation of sexual/familial, 'economic' (property) and membership arrangements. Next follows a discussion of state/nation formation in the tumultuous transition to European modernity and its emerging liberal, capitalist, imperialist and racializing projects. I then review neoliberal economic developments and current conditions of informality, which includes a survey of liberal, marxist and feminist analyses and their policy recommendations. A concluding section draws together key arguments and their implications.